Vyhledávací studie obchvatu obce Lhota Rapotina - Kovářová, Marika (Vysoké učení technické v Brně. Fakulta stavební, 2023)
Předmětem diplomové práce je návrh obchvatu obce Lhota Rapotina, silnice II/374, zpracovaném v podrobnosti studie. Obec Lhota Rapotina se nachází v okresu Blansko v Jihomoravském kraji. Zadáním diplomové práce bylo prověřit možná variantní řešení obchvatu s napojením na stávající a plánovanou okolní infrastrukturu související s výstavbou Boskovické spojky. Cílem bylo mj. navrhnout takové řešení, které sníží intenzitu dopravy v obci (zejména vysoký počet nákladních vozidel přepravujících materiál z přilehlého kamenolomu). Byly vypracovány 3 varianty obchvatu; východní a západní. Ze zpracovaných variant byla k bližšímu zkoumání vybrána varianta západního obchvatu navržená v kategorii S9,5/90, která respektuje polohu plánované Boskovické spojky a která současně slouží jako protipovodňové opatření obce.

The subject of the diploma thesis is the design of the bypass of the village Lhota Rapotina, road II/374, processed in the details of the study. The village of Lhota Rapotina is located in the Blansko district in the South Moravian Region. The task of the diploma thesis was to examine possible alternative solutions of the bypass with connection to the existing and planned surrounding infrastructure related to the construction of the Boskovice – connecting road. The aim was, among others, to propose a solution that would reduce the traffic intensity in the village (especially the high number of trucks transporting material from the adjacent quarry). Three variants of the bypass were developed; eastern and western. From the developed variants, the western bypass variant designed in the S9.5/90 category was selected for closer examination, which respects the location of the planned Boskovice - connecting road and which also serves as a flood protection measure for the village.
Lhota Rapotina bypass - location study
Keywords: Lhota Rapotina; vyhledávací studie obchvatu; II/374; obchvat obce Lhota Rapotina; Lhota Rapotina; bypass location study; II/374; bypass of the village Lhota Rapotina